The Corporate State: Historical Prospective on International Industrial Relations - Bleas , Harry (Journal of Law and Governance, 2015)
Since the 1970s transnational corporations have increasingly sought to move business to locations where labour was cheapest. They saw this as an opportunity to maximize profit and reduce tax. The paper compares the experiences of Singapore and Hong Kong, the first wave of countries to open their markets to foreign corporations, with other countries such as Bangladesh and Myanmar which are the latest countries to enter into the ‘cheap labour for hire’ business. The paper argues that countries that do not have strong government policies face having their country being used for forced labour by unscrupulous corporations and individuals seeking to make huge profits.